Replication, evocation and revocation of linguistic sexism in translated national anthems - Samson Olasunkanmi Oluga,; Teh, Chee Seng; Gerard Sagaya Raj Rajoo, (Penerbit Universiti Kebangsaan Malaysia, 2016)
There is persistent linguistic sexism in the anthems of some countries that are members of the United Nations which diametrically negates the principle of gender equality and the global condemnation of gender-biased language use, especially in public communication. This can be very serious because anthems represent unique symbols of national identity that epitomise nations whose male and female citizens deserve equal recognition and representation. This paper presents the outcome of a linguistic investigation of selected fifty-eight translated anthems originally written in some West/North Germanic and Romance/Italic languages. Firstly, this reveals twenty (20) cases of replication of linguistic sexism that originate from the Source Texts (STs) and which are duplicated in the Translated Texts (TTs) of the anthems. Secondly, it discovers thirteen (13) cases of evocation of linguistic sexism in the anthems which do not originate from the Source Texts (STs) but which only emanate from the Translated Texts (TTs) of the anthems. Thirdly, it detects eleven (11) cases of revocation of linguistic sexism where cases of sexism reflected in Source Texts (STs) are neutralised in Translated Texts (TTs) of anthems. The paper then details a Critical Discourse Analysis via the description, interpretation and explanation of the cases of replication, evocation and revocation of linguistic sexism of the translated national anthems. Finally, the paper suggests the need for resolution of linguistic sexism of translated anthems via replacement of misogynistic expressions which are gender-biased with androgynous expressions that are gender-neutral among others.